APPLICABILITY OF BITUMINOUS-BASED INHIBITOR AS CORROSION PREVENTION METHOD IN REINFORCED CONCRETE - Astuti, Pinta (Journal of Applied Engineering Science, 2024)
Corrosion is the most common cause of structural and material degradation in reinforced concrete (RC) constructions. A well-constructed structure protects the embedded steel bar from chloride ions both physically and chemically, which is particularly important for constructions exposed to seawater. Given the significant economic losses caused by corrosion, suitable measures to reduce corrosion in concrete are required. In this study, three-layer of bituminous-based inhibitor was applied to the surface of two steel bars embedded (steel coating) in mortar cement with 3 cm and 5 cm of concrete cover. Portland composite cement (PCC) and Portland pozzolan cement (PPC) was used as a binder material of mortar cement. The cubical mortar cement specimens were fabricated, and exposed to three conditions (e.g., wet condition, dry condition, and dry-wet cycle) until 60 days after 28 days of immersed water curing. The results demonstrated that corrosion prevention employing steel coating techniques by using bituminous-based inhibitor gives superior protection as seen by a higher positive corrosion potential value when compared to non-coating specimens, implying that the coating method may be used to prevent corrosion. This is because the coating process by using bituminous-based inhibitor may prevent ions from entering the reinforcing steel. In all exposure circumstances and with all preventive procedures, a concrete cover with a thickness of 5 cm has a lower corrosion risk, as shown by a higher corrosion potential value, than a concrete cover with a thickness of 3 cm. The larger the thickness of the concrete cover, the more the surrounding ecosystem is protected. The utilization of PPC as binder in concrete maintained the stable corrosion potential value when the coating method applied.
Keywords: bituminous-based inhibitor, corrosion prevention, half-cell potential, PCC, PPC